PENJADWALAN SATPAM JAGA DENGAN ALGORITMA GENETIKA - Loekito, Ronny (PROXIES, 2017)
Schedule is useful to manage activities to be more effective. Schedule can tell what to do and when to do it. Many schedules still set manually, including security guard schedule. This project aims to create a security guard schedule automatically by using Genetic Algorithm which is usually used for schedule optimization. The purpose of this project is to create an effective security guard schedule with desired conditions such as working hours, shifts, and number of guard posts.